2007
DOI: 10.2174/157016207780636533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Highly Active Antiretroviral Therapy on HIV-1-Associated Oral Complications

Abstract: The oral cavity of human immunodeficiency virus type I (HIV-1) infected individuals is subjected to a series of opportunistic infections which are usually considered as a prognostic marker for the severity of infection as well as an indicator of immunodeficiency. The highly active antiretroviral therapy (HAART) has significantly lessened the severity of HIV-associated oral infections although this therapeutic regimen is considered to be responsible for some of the oral lesions such as oral warts and salivary g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 126 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…The rapid establishment and course of necrotizing forms of periodontal disease in patients with HIV/AIDS infection, contrary to the gradually progressing periodontal disease in adults in the general population has been outlined in many studies and had not been reported before AIDS epidemic (Murray et al , 1989; Barr et al , 1992; Yeung et al , 1993a; Murray, 1994). HAART appears to have profoundly influenced the prevalence, severity and course of periodontal lesions as will be further discussed in the next section of the present review (Parveen et al , 2007).…”
Section: Features Of Periodontal Lesions In Hiv‐infected Patientsmentioning
confidence: 86%
See 1 more Smart Citation
“…The rapid establishment and course of necrotizing forms of periodontal disease in patients with HIV/AIDS infection, contrary to the gradually progressing periodontal disease in adults in the general population has been outlined in many studies and had not been reported before AIDS epidemic (Murray et al , 1989; Barr et al , 1992; Yeung et al , 1993a; Murray, 1994). HAART appears to have profoundly influenced the prevalence, severity and course of periodontal lesions as will be further discussed in the next section of the present review (Parveen et al , 2007).…”
Section: Features Of Periodontal Lesions In Hiv‐infected Patientsmentioning
confidence: 86%
“…On the contrary, HAART does not appear to significantly affect the prevalence of periodontal disease in children (Flanagan et al , 2000; Khongkunthian et al , 2001; Parveen et al , 2007).…”
Section: Prevalence Of Periodontal Diseases In Hiv‐infected Individualsmentioning
confidence: 99%
“…Due to advances in therapeutic efficacy and clinical care in developed countries, susceptibility of HIV patients to opportunistic oral infections has been dramatically reduced [37,38]. However, worldwide, where the vast majority of HIV infected individuals do not have access to basic clinical care or therapy, oral complications remain a serious problem [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 50% of PLWH will present oral lesions at some point of the disease evolution, and this number goes up to 80% for the patients in the acquired immunodeficiency syndrome (AIDS) stage ( Lomelí-Martínez et al., 2022 ). Several oral lesions in PLWH are related to bacterial, fungal or viral co-infections (for reviews see de Jesús-Campos et al., 1992 ; Ryder, 2000 ; Parveen et al., 2007 ; Lomelí-Martínez et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%